Quaternary climate change in Iran – the state of knowledge - Kehl, Martin (ERDKUNDE, 2009)
The mostly Mediterranean climate of Iran is governed by the pressure systems of the Siberian High, the Westerly depressions and the SW Monsoon. In the past, the locations and intensities of these systems changed probably causing climate change and affecting landscape evolution in this ecologically diverse country. Recently, new evidence for Quaternary climate change in Iran has been presented. This paper briefly reviews the present state of knowledge and identifies future perspectives of paleoclimatic research in Iran. Paleoclimatic deductions have mainly been based on geomorphic evidence and, more recently, also on stratigraphical investigations including the physical dating of sediments. In northern and western Iran climate changed between dry and cold climatic conditions during the stadials and moist and warm conditions during the interglacials. Lake sediments and loess deposits also suggest moisture increases during interstadials of the Last and Penultimate Glacials. In western Iran, the Younger Dryas and the Lower Holocene were most probably characterized by dry climatic conditions. Overall, the climatic cycles and events known from other parts of the globe are rarely documented in Iran and our picture of past climate change there is patchy and incomplete. More proxy-information and geochronological data are needed, in particular for central and southern Iran. The sedimentary records of lakes and playas as well as loess deposits hold a strong potential to identify climate signals and the paleoclimate information of speleothems or tree-rings has not yet been challenged.